An Innovative Approach for Top-K Spot Monitoring Based On Trust Worthy Data - Renuga, E; Baskaran, S (International Journal of Computer Sciences and Engineering, 2025)
Recommender Systems are established progressively popular in now-a-days and developed in a variety of zones counting master's associates, jokes, and eateries, articles of clothing, budgetary administrations, life coverage, emotional accomplices and Twitter pages. The proficient management of record streams assumes an essential part in abundant information filtering systems. A focal server displays the archive stream and constantly reports to every client the best k records that are most appropriate to catch phrases. By using estimated procedure client can discover top k result in light of put stock in admirable information. The approach gives perpetual best k spot brings about powerful path by engaging data mining measures. The proposed organization helps user to download trust worthy data based on only the amount of files transferred by users not based on ratings and assessments. This technique filter outs the unworthy data from the whole evidence. It coordinates rating and puts stock in data to progress the rating positioning model, which adequately augments the nature of the best k thing depressed of all clients. A development of tests on genuine datasets establishes the competence of our intention